Evaluasi Sistem Informasi Kendaraan (GF Service) di Binus University Berdasarkan Kerangka Cobit pada Domain Delivery and Support - Udiono, Tangkas; Budi, Haris Setia; Mariyani, Mariyani (Bina Nusantara University, 2015)
Information Systems Audit is an activity that is carried out in a company that aims to ensure compliance with existing policies. General Services is one of the units in BINUS University whose activities in the form of services such as Transportation and Document Courier, Copy Centre and General Facility.However, this study is limited to the Transportation and Document Courier unit that uses an online reservation application gfservice.binus.ac.id. Maturity level of the existing information systems in Directorate General Services specifically Transportation and Document Courier based on COBIT Maturity Model is 2,951(Repeatable but Intuitive) or approaching from the standards set by the International is 3:00, which means the process has been documented and communicated well. This study also conducted an evaluation of the quality ofinformation systems and quality of information available. The result is positive impact on users' satisfaction, that means the increases of information quality and the quality of information systems of GF Services would increase student and employee satisfaction, but it also explained the factors that affect success utilization of existing information systems in order to rise to the level to 4, which means managed and Measurable. The results of the regression analysis and correlation between the quality factors of information systems and the quality ofinformation on student satisfaction and employee are 38.2% and 48.1%; while the rest is influenced by other factors not addressed in this study.